GAYA HIDUP DAN KEJADIAN HIPERTENSI PADA STAF DI PUSKESMAS KARADENAN, PUSKESMAS BOJONGGEDE DAN PUSKESMAS RAGA JAYA KABUPATEN BOGOR TAHUN 2022 - Nurul Fajriah (2022)
Hypertension is also called the silent killer, where people with hypertension do not immediately know if they have hypertension before checking their blood pressure. Hypertension is a fairly common disease because many people in Indonesia suffer from it. Hypertension is strongly influenced by an unhealthy lifestyle. Several risk factors are thought to have a role in the occurrence of hypertension, namely lifestyle such as diet, physical activity, smoking, fasting and adequate rest time. The purpose of this study was to determine the relationship between lifestyle and the incidence of hypertension. This cross sectional research on April until June 2022 was followed by 83 staff at Karadenan, Bojonggede, and Raga Jaya health center by means of total sampling. The average respondents ranged from 21-35 years old with the majority being female. bachelor education background, Muslim and working as a civil servant. Multivariate analysis showed diet (p=0.010 OR=0.163) as the risk factor most associated with the incidence of hypertension. The conclusion is diet greatly affects the occurrence of hypertension. Advice that can be given is to maintain a healthy diet is one of the factors that can prevent hypertension.